Aristotle's "Metaphysics" Lambda - New Essays - Horn, Christoph; Horn, Christoph (Philosophie der Antike, 2016)
The treatise known as book Lambda of Aristotle’s Metaphysics has become one of the most debated issues of recent scholarship. Aristotle adresses here fundamental questions of his theory of substance, his idea of causes and principles, and his concept of motions. Furthermore, the importance of the text is due to the fact that it contains an outline of what was traditionally understood as Aristotle’s theology.